The Effectiveness of Reflective Practice with Video Recording on English Teachers' Teaching Performance - Ramadhani Sundari; Sitti Fatimah (Journal of English Language Teaching, 2022)
This research is an experimental research. This research employed pre-experimental design using quantitative approach with one group pre-test and post-test design. The quantitative data are obtained from the teacher's final video recording. The research aims to determine the effectiveness of reflective practice with video recording on English teachers’ teaching performance in UNP. The population of this research was English teachers of PPG participants of Universitas Negeri Padang in Academic Year 2021. The research sample was 19 In-service English Teachers of Teachers Certification Program (PPG) of Universitas Negeri Padang. As this is the quantitative research, the researcher used the Paired Sample T-test in SPSS 22 for Windows to analyze the data. It is found that the mean score of teachers’ teaching performance has decreased by 4.21 points, bringing the average score down from 83.49 to 79.28. Therefore, the degree of significance of 2.5% or 0.025 was used by the researcher, hence, it is found that the significance (2-tailed) value on teachers’ teaching performance was 0.029 > 0.025 which means that H0 was accepted and Ha was rejected. Based on the research results, it can be concluded that the use of reflective practice with video recording has no significant effect on English teachers’ teaching performance.